RANCANG BANGUN MODEL LATIHAN KOSAKATA BAHASA INGGRIS TEKNIK BERBASIS MULTIMEDIA - Yogi Widiawati; Anik Tjandra; Sri Danaryani (Epigram, 2018)
AbstractThis is an extensive research based on the prior research conducted in 2010 which was called “The Frequency of Technical English Usage Used by Students of Electronics Department”. This research is aimed to facilitate the students of all polytechnics in Indonesia in general, especially State Polytechnics of Jakarta, where this research was applied. The result of this research is a kind of software which is easily used and portable so that the students can use the software anywhere and anytime. It consists of 3 (three) sections of exercises. At the end of each exercise, the students are evaluated automatically by looking at the scoring system. These will encourage them to get good score by repeating it again and again. So the technical words are not problem for them. Furthermore, the students can practice technical English vocabulary both at home and in the language laboratory by using this software.Keywords: English Technical Vocabulary, Software, portableAbstrakPenelitian ini dilalukan berdasarkan penelitian sebelumnya yang dilakukan pada tahun 2010 yang berjudul “Kekerapan Penggunaan Kosakata Bahasa Inggris Teknik yang digunakan Mahasiswa Jurusan Teknik Elektro”. Penelitian ini dibertujuan untuk memfasilitasi mahasiswa untuk berlatih kosakata bahasa Inggris Teknik. Karena hasil penelitian ini berupa perangkat lunak maka perangkat ini dapat digunakan kapan saja dan dimana saja. Perangkat ini terdiri dari 3 bagian latihan. Dan pada akhirnya diberikan hasil evaluasi dengan sistem penilain. Hal ini akan memotivasi mahasiswa untuk belajar lebih giat lagi.Kata Kunci: kosakata bahasa Inggris teknik, perangkat lunak, mudah dibawa